(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Objective- To study the varying presentations of 10 cases diagnosed with Paediatric Cholesteatoma in a Tertiary Care Hospital Study Design- A prospective study of 10 patients from January 2025 to January 2026 Subject And Methods- Patients who presented to the ENT OPD of our hospital were admitted and examined in detail. Patients were then planned for Canal Wall Up or Canal Wall down mastoidectomy. Histopathological Diagnosis was used to confirm Cholesteatoma and then the patients were studied based on age, sex, presenting chief complaints, examination and radiological findings. Results- In our study done over a period of 1 year, we diagnosed and managed 10 cases of cholesteatoma in paediatric age group (<18 years). 60% of the patients were male. Most of the patients were belonging to the age group of 6-8 years and were having hailing from a rural residential area. The commonest chief complaint was foul smelling ear discharge and the most common otological finding was the presence of retraction pocket. The diagnosis was done clinically and radiologically with the help of High Resolution CT of Temporal Bone and the patients underwent Canal wall up or Canal wall down mastoidectomy. Histopathological confirmation of the diagnosis was done and patients were followed up for any recurrence. Conclusion- This study, done in a tertiary care hospital helps to analyse the patients who presented to ENT OPD in order to facilitate the establishment of a diagnosis based on clinical signs and symptoms and also to understand any underlying eustachian tube and palatal dysfunctions which likely contribute to the elevated risk of developing Cholesteatoma in a paediatric age group. Additionally, cholesteatoma in this population was diagnosed and required surgical intervention at a younger age, which may suggest a more aggressive disease course. Providers should maintain a high degree of suspicion for cholesteatoma in this complex population.